IMPLEMENTATION OF THE GOVERNMENT'S DISCRETION IN INDONESIA, AUTHORITY, AND RESPONSIBILITY IN THE MANAGEMENT OF GOVERNMENT - Nur Ro`is; Tri Yani; Putri Mayang Sari; Dewi Ary Nurdiana Putri; Lupi Mardiansyah (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
The research entitled